The trogocytosis of neutrophils on initial transplanted tumor in mice - Mengru Zhu; Shengnan Wang; Kuo Qu; Feiyu Lu; Mengyuan Kou; Yunpeng Yao; Tong Zhu; Yongli Yu; Liying Wang; Chaoying Yan (iScience, 2024)
Summary: The role of neutrophils in tumor initiation stage is rarely reported because of the lack of suitable models. We found that neutrophils recruited in early tumor nodules induced by subcutaneous inoculation of B16 melanoma cells were able to attack tumor cells by trogocytosis. The anti-tumor immunotherapy like peritoneal injection with TLR9 agonist CpG oligodeoxynucleotide combined with transforming growth factor β2 inhibitor TIO3 could increase the trogocytic neutrophils in the nodules, as well as CD8+ T cells, natural killer (NK) cells, and their interferon-γ production. Local use of Cxcl2 small interfering RNA significantly reduced the number of neutrophils and trogocytic neutrophils in tumor nodules, as well as CD8+ T and NK cells, and also enlarged the nodules. These results suggest that neutrophils recruited early to the inoculation site of tumor cells are conducive to the establishment of anti-tumor immune microenvironment. Our findings provide a useful model system for studying the effect of neutrophils on tumors and anti-tumor immunotherapy.